Multimodal Atlas of the Murine Inner Ear: From Embryo to Adult - Bryant, Jean-Paul; Chandrashekhar, Vikram; Cappadona, Anthony J.; Lookian, Pashayar P.; Chandrashekhar, Vibhu; Donahue, Danielle R.; Munasinghe, Jeeva B.; Kim, H. Jeffrey; Vortmeyer, Alexander O.; Heiss, John D.; Zhuang, Zhengping; Rosenblum, Jared S. (Frontiers in Neurology, 2021)
The inner ear is a complex organ housed within the petrous bone of the skull. Its intimate relationship with the brain enables the transmission of auditory and vestibular signals via cranial nerves. Development of this structure from neural crest begins in utero and continues into early adulthood. However, the anatomy of the murine inner ear has only been well characterized from early embryogenesis to post-natal day 6. Inner ear and skull base development continue into the post-natal period in mice and early adulthood in humans. Traditional methods used to evaluate the inner ear in animal models, such as histologic sectioning or paint-fill and corrosion, cannot visualize this complex anatomy in situ. Further, as the petrous bone ossifies in the postnatal period, these traditional techniques become increasingly difficult. Advances in modern imaging, including high resolution Micro-CT and MRI, now allow for 3D visualization of the in situ anatomy of organs such as the inner ear. Here, we present a longitudinal atlas of the murine inner ear using high resolution ex vivo Micro-CT and MRI.